ANALISIS POTENSI PERTUMBUHAN SEKTOR PERTANIAN DI PROVINSI LAMPUNG - Tungga Buana Diana; Imas Wildan Rafiqah (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the growth potential of the existing sub-sectors in the agricultural sector of Lampung Province. This research uses Location Quotient (LQ) analysis, Shift-Share (SS) analysis, and Klassen typology. The results showed that the location quotient in the agricultural, forestry, and fishery sectors was the highest base sector in Lampung Province. The agricultural sub-sectors included in the basic sector are the agricultural and hunting services sub-sector, the food crops sub-sector, the livestock sub-sector, the fisheries sub-sector, the plantation sub-sector, and the horticulture sub-sector. In the Shift-Share analysis, the agricultural sub-sectors that have a proportional shift (P) value in the progressive category are the fisheries sub-sector, the plantation sub-sector, the livestock sub-sector, and the horticultural crop sub-sector. In the Differential shift (D) component, the sub-sector that has a positive value is the livestock sub-sector, meaning it has good competitiveness. Furthermore, in the Klassen Typology analysis, the sector that is included in the prime sector category is the livestock sub-sector. The sub-sectors included in the potential sector are the food crops sub-sector, the plantation sub-sector, and the fishery sub-sector. In addition, three sub-sectors are underdeveloped including the horticulture sub-sector, the agricultural and hunting services sub-sector and the forestry and logging sub-sector. Based on the three analytical methods, the livestock sub-sector is the leading sub-sector of the economic sector in Lampung Province. This is because the livestock sub-sector has a positive value from the three data analysis methods.